EFEKTIFITAS KELEMBAGAAN KOMNAS PEREMPUAN DALAM PERLINDUNGAN HAM BAGI PEREMPUAN DI INDONESIA - Rommy Patra (Masalah-Masalah Hukum, 2012)
Abstract: National Commission on Violence Against Women (Komnas Perempuan) is an independent national institution that function to promote and protect women's rights. Institutional existence of Komnas Perempuan still contain many flaws and does not show the characteristics as effective human rights institution. Therefore the institutional of Komnas Perempuan should be arranged to strengthen the function in the protection of human rights in Indonesia, especially women's rights. Keyword: National Commission on Violence Against Women, effective, institutional Abstrak: Komisi Nasional Anti Kekerasan terhadap Perempuan (Komnas Perempuan) adalah institusi nasional independen HAM yang berfungsi memajukan dan melindungi hak-hak perempuan. Eksistensi kelembagaan Komnas Perempuan masih mengandung banyak kelemahan dan tidak memperlihatkan ciri sebagai institusi nasional HAM yang efektif. Oleh karena itu kelembagaan Komnas Perempuan harus ditata untuk memperkuat perlindungan HAM di Indonesia khususnya hak-hak perempuan. Kata Kunci: Komnas Perempuan, efektif, kelembagaan